FRI0015 Treating rheumatoid arthritis to target: is low disease activity good enough?. (12th June 2018) - Nikiphorou, E.; Norton, S.; Young, A.; Carpenter, L.; Dixey, J.; Walsh, D.; Kiely, P.; ,
Abstract : Background: Treat-to-target (T2T) principles in rheumatoid arthritis (RA) are now widely recognised as effective in achieving optimal disease outcomes. Objectives: To examine for differences in outcomes between low (LDAS) and remission (RDAS) disease activity score (DAS) categories, addressing the question: is LDAS a 'good enough' treatment target in RA? Methods: Data from two consecutive UK multi-centre RA inception cohorts with similar design were used: the Early RA Study (ERAS) and Early RA Network (ERAN). Recruitment figures/median follow up for ERAS and ERAN were 1465/10 years (maximum 25 years), and 1236/6 years (maximum 10 years) respectively. Standard demographic and clinical variables were recorded at baseline and then annually until the end of study follow up. Disease activity was categorised by mean DAS28 score between years 1–5 as remission [mRDAS <2.6] or low [mLDAS 2.6–3.2]; as sustained low/remission DAS (sLDAS/sRDAS) based on DAS persisting in each of the two categories at years 1–2 and as Boolean remission (years 1–2). Change in HAQ and SF36 (physical [PCS] and mental [MCS] components) for each disease activity category were modelled using linear mixed models with time incorporated as a linear spline with change-point at 12 months. Year of onset, age, gender and use of steroids or conventional DMARDS at first visit were included as covariates. Results: Out of 2701 patients, 468 (17%) were in mRDAS, 284 (11%) in mLDAS in the first five years of disease. Lower proportions had achieved sRDAS (8%), sLDAS (6%) and Boolean (2%) remission. Mean age was similar across categories; more women were in low vs remission DAS. Compared to mLDAS or sLDAS, inflammatory markers, DAS, functional (HAQ, PCS) and mental (MCS) scores tended to be better in the mRDAs, sRDAS or Boolean remission categories (figure 1). Significant differences (p<0.05) were noted between the mRDAS and mLDAS between years 1–5 for all outcomes; for sRDAS compared to sLDAS, the difference was significant at one year but not by five years. Conclusions: The results demonstrate striking differences between remission and low DAS categories, suggesting worse functional and SF36 outcomes over time in the low DAS categories. This supports that remission should be the primary T2T goal in in RA. Disclosure of Interest: None declared